Waste Cleaning Waste: Photodegradation of Monochlorophenols in the Presence of Waste-Derived Photosensitizer - Avetta, Paola (2013)
Soluble bio-based substances (SBO) have been isolated from urban waste. Their structural similarity with natural organic matter suggested exploring their activity in the photodegradation of organic substrates. In this work, they are shown to promote the photodegradation of monochlorophenols. Experiments performed with 1.0 × 10−4 M substrate solutions irradiated by simulated solar light in the presence of SBO showed the progressive degradation of all the probe substrates. The experimental data were fitted to a pseudo-first-order kinetics, and the rate constant was found to decrease in the following order: 2-chlorophenol > 3- chlorophenol > 4-chlorophenol. The effect of pH and SBO concentration on chlorophenols degradation was assessed. Experiments performed in the presence of selective scavengers along with EPR measurements supported the main role of singlet oxygen in the substrate photo degradation mechanism. Toxicity assays showed that the photodegradation of chlorophenols in the presence of SBO is accompanied with a progressive up to complete detoxification of the system. Moreover, no significant contribution of SBO to the whole system toxicity was observed. The results show how urban wastes can be a resource of photosensitizing bio-based substances to be explored in wastewater treatments.